Student’s Attendance System Using QR Code - Zakaria, Normah; Mohd Nasir1, Muhamad Alfie Yazid; Hamzah, Norhasyimah Hamzah; Rubani, Siti Nur Kamariah; Ariffin, Arihasnida (Research and Innovation in Technical and Vocational Education and Training, 2021)
The purpose of this project is to develop a system that can record the presence of students using QR code. Previously, teachers needed to use paper to record student attendance. There are many problems that arise when teachers use paper as a record of student attendance such as loss of attendance record and have been taken a long time. The objective of the study is to design a prototype interface of student attendance system using QR code and casing of QR code scanner, to build up the design the prototype interface of student attendance system using QR code and casing of QR code scanner and test the functionality the prototype of interface student attendance system using QR code and casing of QR code scanner. The interface for this system will be integrated with the LabVIEW Software to develop a database. This system can record the attendance of the student to school and a warning letter will be automatically generated when the student does not come to school in two days repeatedly. The development process of the Student Attendance System Using QR Code is based on Prototype Development Model  that  consists  of  five-phase  model,  that  is  planning,  analysis,  design,  Prototype development,  and  testing.  The  design  of  casing  for  QR  code  scanner  was  developed  using Sketchup  software.  LabVIEW  Software  is  used  to  generate  interface  display  and  built-in database using Microsoft Excel. Overall, the system that has been developed can works well and achieves the objectives set.